2014
DOI: 10.1039/c4cs00078a
|View full text |Cite
|
Sign up to set email alerts
|

Water adsorption in MOFs: fundamentals and applications

Abstract: This review article presents the fundamental and practical aspects of water adsorption in Metal-Organic Frameworks (MOFs). The state of the art of MOF stability in water, a crucial issue to many applications in which MOFs are promising candidates, is discussed here. Stability in both gaseous (such as humid gases) and aqueous media is considered. By considering a non-exhaustive yet representative set of MOFs, the different mechanisms of water adsorption in this class of materials are presented: reversible and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
863
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,186 publications
(918 citation statements)
references
References 175 publications
23
863
1
4
Order By: Relevance
“…The stability of CuBTC in the presence of water has been studied many times and it was shown that hydrolysis reactions can lead to destruction of the MOF structure 43,46,47 . Therefore, water is generally unsuitable, for example, as an extraction medium to remove confined molecules from the porous matrix of the MOF.…”
Section: Stability Of Cubtc In Acetone Isopropanol and Methanolmentioning
confidence: 99%
“…The stability of CuBTC in the presence of water has been studied many times and it was shown that hydrolysis reactions can lead to destruction of the MOF structure 43,46,47 . Therefore, water is generally unsuitable, for example, as an extraction medium to remove confined molecules from the porous matrix of the MOF.…”
Section: Stability Of Cubtc In Acetone Isopropanol and Methanolmentioning
confidence: 99%
“…In some recent reviews by Canivet and Burtch, the limits and promises of the MOF stability towards water are treated. 280,281 In a previous pioneering paper by Low, a good overview of the steam stability of MOFs as a function of temperature is given. 282 In many studies on steam stability of MOF membranes, the tests have been carried out only for short periods of time (1-2 days) and it is hard to make conclusions on the long-term stability.…”
mentioning
confidence: 99%
“…Metal-organic framework (MOF) is a class of crystalline hybrid porous material that represents a great source of potential structures for sorption applications, because of their tunable chemical and topological features [4]. Most of these solids are superior to other microporous materials in terms of internal surface area and micropore volume.…”
Section: Introductionmentioning
confidence: 99%